The Role of Inflammatory, Anti-Inflammatory, and Regulatory Cytokines in Patients Infected with Cutaneous Leishmaniasis in Amazonas State, Brazil - Espir, Thaís Tibery; Figueira, Luanda de Paula; Naiff, Maricleide de Farias; Costa, Allyson Guimarães da; Ramalho-Ortigão, Marcelo; Malheiro, Adriana; Franco, A. M. (Journal of Immunology Research, 2014)
The authors discuss in this paper the role of inflammatory, anti-inflammatory, and regulatory cytokines in patients infected with different species of Leishmania in Amazonas State, Brazil. A comparative analysis was made of serum concentrations of these cytokines in the peripheral blood of 33 patients infected with cutaneous leishmaniasis. The isolates were identified as Leishmania guyanensis, L. naiffi, and L. amazonensis. Most (64%) of the patients were male ranging in age from 18 to 58 years. Protein expression profiles of IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF-α, and IL-17 cytokines were shown to vary significantly between infected and noninfected (control group) individuals and according to the Leishmania species. Infection caused by L. guyanensis accounted for 73% of the cases and patients with this parasite also showed higher concentrations of IL-2, IFN-γ, IL-4, and IL-17 when compared to infection by L. amazonensis. Patients with infection caused by L. naiffi showed higher concentration of the cytokines analyzed when compared to uninfected patients; however, there was no statistically significant difference with the other species analyzed. © 2014 Thaís Tibery Espir et al.
Keywords: Cytokine; Gamma Interferon; Interleukin-10; Interleukin-17; Interleukin-2; Interleukin-4; Interleukin-6; Tumor Necrosis Factor-alpha; Autacoid; Cytokine; Gamma Interferon; Interleukin-10; Interleukin-17; Interleukin-2; Interleukin-4; Interleukin-6; Tumor Necrosis Factor-alpha; Adult; Antiinflammatory Activity; Clinical Comparative Study; Controlled Study; Female; Human; Leishmania; Leishmania Naiffi; Male; Nonhuman; Protein Blood Level; Protein Expression; Skin Leishmaniasis; Adolescent; Blood; Classification; Flow Cytometry; Host Parasite Interaction; Immunology; Middle Aged; Parasitology; Physiology; Skin Leishmaniasis; Species Difference; Young Adult; Adolescent; Adult; Cytokines; Female; Flow Cytometry; Host-parasite Interactions; Humans; Inflammation Mediators; Interferon-gamma; Interleukin-10; Interleukin-17; Interleukin-2; Interleukin-4; Interleukin-6; Leishmania; Leishmania Guyanensis; Leishmaniasis, Cutaneous; Male; Middle Aged; Species Specificity; Tumor Necrosis Factor-alpha; Young Adult